CHALLENGES IN TRANSLATOR TRAINING: DESIGN AND EVALUATION OF A MOBILE APP LOCALIZATION MODULE - Sánchez Ramos, María del Mar (2017)
Aware of the unstoppable advance of localization and its influence on the translation industry, this paper aims at providing a mobile application localization module for the translator curriculum. With this goal in mind, we describe the teaching module conducted with 24 undergraduate translator trainees as part of the Localization course (Degree in Modern Languages and Translation, University of Alcalá, Spain). Following a socio-constructivist methodology, qualitative data were collected via a group session and a questionnaire, which allowed evaluating the teaching proposal. Upon examination of the results, we can state that the main challenges are related to linguistic and technical issues and that their training is a must if we want our students to be ready for what comes ahead.